Introduction to Biological Networks and their Contributions to Systems Biology - Khushboo; Pulkit Singh; Shazia Haider (International Journal of Bioinformatics and Computational Biology, 2024)
Biological networks provide a conceptual framework to represent and analyze the intricate interconnections among the numerous components that make up living systems. This review paper elucidates the foundational principles of networks and their diverse applications in systems biology, highlighting their crucial role in understanding the inherent complexity of biological processes. Utilizing graph theory, these networks represent entities like genes, proteins, and metabolites as nodes, with their interactions depicted as edges. The review explores core graph theory elements such as nodes, edges, hubs, and motifs, essential for network analysis. It delves into topological parameters like degree, centrality measures, and clustering coefficients, quantifying structural properties and connectivity patterns, and offering insights into network organization and dynamics. Additionally, the review comprehensively examines various biological networks, including protein-protein interaction networks, gene regulatory networks, metabolic networks, cell signaling networks, and ecological networks, highlighting their distinct characteristics and applications. Network visualization techniques, such as force-directed layouts and circular representations, are also explored, facilitating effective communication of complex network structures. The integration of omics technologies with network analysis is addressed, emphasizing the importance of mathematical modeling in deciphering disease mechanisms across multiple scales. The review also underscores the application of network-based approaches in identifying potential drug targets and understanding complex diseases like cancer and diabetes. Overall, this comprehensive review provides an exhaustive introduction to biological networks, their theoretical foundations, analytical tools, and applications in systems biology, accentuating their pivotal role in unraveling the intricacies of living systems and paving the way for future advancements in biomedical research and personalized medicine.
Keywords: Biological network; graph theory; network biology; therapeutics; topological parameters